Peningkatan Kemampuan Anak dalam Mengenal Warna dengan Menggunakan Media Balok di TK PGRI Al Hidayah - Dina Hidayana; Debby Adelita Febrianti Purnamasari (Zuriah Jurnal Pendidikan Anak Usia Dini, 2023)
This research is motivated by the importance of children's ability to recognize colors using block media. The problems that occur in children are caused by the child's lack of motivation to learn, as well as parents' thoughts that put aside knowledge about recognizing colors, parents only tend to prioritize knowledge of letters and numbers. The aim of this research is only to determine the increase in children's ability to recognize colors using block media in Group A of PGRI AL Hidayah Kindergarten. This type of research is in the form of classroom action research (PTK). The subjects of this research were group A of TK PGRI AL Hidayah 22 children consisting of 11 boys and 10 girls. The research procedures used were planning, action, observation and reflection. The results of the classroom action research showed that in the pre-cycle, 4 children or 25% had achieved completeness in recognizing colors during learning, in the first cycle of the first round using good block media, 6 children or 35%, in the second cycle of the first round, 8 children or 40% were good. . By using block media, children's completeness in recognizing colors during learning in cycle II, round I, was 10 children, 45%, cycle II, second round, which was classified as good, there were 12 children or 65%. Based on the research results, it can be concluded that color recognition activities using block media can improve children's ability to recognize colors in group A of TK PGRI Al Hidayah.